How Homosexuals Were Barred from Federal Employment by the Eisenhower Government in the 1950s - Zeng, Lanshu (Transactions on Social Science, Education and Humanities Research, 2025)
Amid the Cold War hysteria of the 1950s, the U.S. government also pursued a separate purge known as the “Lavender Scare,” which ousted lesbians and gay men from federal employment. The official justification was national security and the fears of potential blackmail, but the real reason, as this article suggests, lay deeper: legacy homophobia thrived on a postwar era of heightened prudery. By way of a rhetorical analysis of documents' figurative language, this article first unpacks the euphemizing code of a 1951 Congressional Report to reveal, via a preexisting medicalization of homosexuality and codification of bias to bureaucratic rule, a narrative of homosexuals as inherently unstable "sexual perverts". The paper then deconstructs the gut-level rhetoric of politicians like Senator Miller, revealing his reliance on particular types of McCarthyism as a strategy to weaponize moral panic and to conflate the homosexual threat with the communist threat. The paper argues that the logic of the Lavender Scare was circular, with state-sponsored homophobia producing the very conditions of vulnerability it purported to defend against. Ultimately, the study exposes the harm evoked by these sensations, which not only ruined innumerous lives, but paradoxically served to incite the formation of some of the first homophile rights organizations, demonstrating the staggering ease with which bigotry may be legalized under the rhetoric of national security.